A magnesium-based composite hydrogen storage material based on multi-catalyst nanoclusters and a preparation method thereof

The one-pot method synthesized mesoporous nanospheres supported by catalytic metals and composited with magnesium-based materials solves the problems of uneven distribution and inefficiency of catalysts in the prior art, and realizes efficient preparation of magnesium-based hydrogen storage materials, significantly improving hydrogen storage and kinetic performance.

CN119735162APending Publication Date: 2025-04-01Liupanshan Laboratory
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411829147.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art cannot introduce binary or multivariate nanocatalytic metal clusters into magnesium-based hydrogen storage materials through simple and safe steps, resulting in low catalytic efficiency and reduced hydrogen storage capacity.

Method used

A one-pot method is used to synthesize binary and multivariate catalytic metal-loaded mesoporous nanospheres and composite them with traditional magnesium-based solid hydrogen storage materials to achieve nano-scale mixing and uniform distribution of catalytic elements.

Benefits of technology

It significantly improves the synergistic catalytic efficiency of binary and multivariate catalytic systems, improves the hydrogen storage performance of magnesium-based materials, reduces the hydrogen absorption and release reaction temperature, and improves the kinetic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735162A_ABST
    Figure CN119735162A_ABST
Patent Text Reader

Abstract

The present invention discloses a magnesium-based composite hydrogen storage material based on multi-catalyst nanoclusters and a preparation method thereof, which belongs to the technical field of efficient hydrogen storage of magnesium-based solid-state hydrogen storage materials. Specifically, the present invention first prepares binary and multi-element transition metal TM‑MNPs, and then uses TM‑MNPs to prepare binary and multi-element TM‑MNPs@MgH2 composite hydrogen storage materials. Compared with the binary and multi-element TM‑MNPs@MgH2 magnesium-based composite hydrogen storage materials prepared by the present invention, the temperature of hydrogen absorption and desorption reaction is significantly reduced, and the kinetics is greatly improved; the preparation process of the present invention is simple, the material synergistic catalytic efficiency is good, the operability is strong, and the preparation cycle is short and the output rate is high; the required raw materials are cheap and easy to obtain, the preparation process cost is low and the safety is high, and it is suitable for industrial mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of efficient hydrogen storage of magnesium-based solid-state hydrogen storage materials, and in particular to a magnesium-based composite hydrogen storage material based on multi-catalyst nanoclusters and a preparation method thereof. Background Art

[0002] As one of the most anticipated new energy sources in the 21st century, hydrogen energy has received more and more attention. Its application has many advantages, such as: the calorific value of hydrogen combustion reaches 142.351 kJ / kg, which is three times that of traditional gasoline, and its source is wide, the combustion product is pure water, and there is no pollutant emission. However, the efficient and safe storage technology of hydrogen is an urgent problem that restricts the rapid development of the hydrogen energy economy. At present, the industrial and laboratory hydrogen storage technology is mainly gaseous hydrogen storage in steel cylinders. The safety of hydrogen cylinders is poor, the volume hydrogen storage capacity is low, and the hydrogen storage capacity of steel cylinders is only 1wt% (15MPa). Liquid hydrogen storage needs to be maintained below the temperature of liquid nitrogen, consumes huge energy, and is expensive. It is mostly used in the aerospace field, and its actual civilian value is not high. Compared with the above two main hydrogen storage methods, solid-state hydrogen storage technology is considered to be one of the most promising hydrogen storage solutions due to its safety and its high hydrogen storage density. Among the many hydrogen storage materials, various metal hydrides have broad application prospects as hydrogen storage materials. For example, the theoretical hydrogen storage capacity of magnesium-based hydrogen storage material MgH2 can reach 7.6wt%, with excellent reversible hydrogen absorption and desorption performance, and can stably exist in the air. Moreover, as a common metal element, metal Mg is abundant in reserves and cheap. However, due to the stable thermodynamic properties (hydrogen absorption and desorption enthalpy change = ±75kJ / molH2) and poor hydrogen absorption and desorption kinetics of magnesium hydride material itself, its desorption temperature is above 350°C, which is not conducive to its practical application.

[0003] In order to improve its thermal / dynamic properties, metals, oxides, halides, etc. are often added as catalysts for catalytic modification. Since different catalysts have different catalytic effects and action mechanisms on magnesium-based hydrogen storage materials, two or more catalyst systems are often used for synergistic catalysis. The two main methods for adding binary and multi-component catalysts under the existing technology are mechanical ball milling and liquid phase co-precipitation. The high-energy ball milling method of directly adding relevant metal catalysts has uneven catalyst distribution and poor synergistic catalytic effect. The chemical solvent reduction method is another similar existing technology that uses a strong reducing agent to co-precipitate and reduce Mg-based materials and catalysts in a specific organic solvent.

[0004] As mentioned above, the main methods for adding catalysts to magnesium-based materials and preparing composites are mechanical ball milling and liquid phase co-precipitation. However, there are many problems: mechanical ball milling cannot achieve nano-mixing of binary or multi-component catalysts and their uniform distribution on the surface of the substrate. The segregated catalytic metal clusters greatly reduce the efficiency of micro-region synergistic catalysis, and increasing the number of catalysts significantly reduces the maximum hydrogen storage capacity of the composite. Another method, liquid phase co-precipitation, takes into account the high activity of magnesium, poor safety and must be operated in a glove box. The reaction conditions are harsh and it is very easy to combine with water and oxygen to cause pollution and spontaneous combustion. And considering the chemical properties of different catalyst salts, the specific operating steps are very complicated, the cost is high, and it is difficult to prepare them industrially in large quantities. In summary, the existing technical solutions cannot introduce binary or multi-component nano-catalytic metal clusters that can be mixed in micro-regions and uniformly distributed in magnesium-based hydrogen storage materials through simple and safe steps.

[0005] Therefore, based on the problems existing in the prior art, providing a method for producing high-performance magnesium-based hydrogen storage composite materials that is simple, safe and suitable for mass production is a technical problem that technicians in this field urgently need to solve. Summary of the invention

[0006] In view of this, the present invention provides a method for preparing high-performance magnesium-based hydrogen storage composite materials that is simple, safe and suitable for mass production: mesoporous nanospheres (hereinafter referred to as MNPs) loaded with binary and multi-component catalytic metals are synthesized by a one-pot method, and composited with traditional magnesium-based solid hydrogen storage materials as precursors, and nano-scale mixing and uniform distribution of multi-component catalytic metal clusters on the surface of magnesium-based materials are achieved under simple process conditions, achieving the purpose of effectively improving the synergistic catalytic efficiency of binary and multi-component catalytic systems and improving the hydrogen storage performance of magnesium-based materials. The present invention uses nanospheres as catalytic media to successfully load catalytic elements in nanometer size, and ensures the uniform distribution of catalytic elements with nano-microspheres in the subsequent preparation process of high-efficiency catalytic magnesium-based composite hydrogen storage material systems, solving the technical problem that multi-component catalysts in the field cannot achieve nano-dispersed distribution and low catalytic efficiency.

[0007] To achieve the above object, the present invention adopts the following technical solution:

[0008] A method for preparing a magnesium-based composite hydrogen storage material based on multi-catalyst nanoclusters comprises the following steps:

[0009] (1) Preparation of binary and multi-element transition metal TM-MNPs

[0010] (1.1) First, dioctyldimethylammonium chloride and sodium hydroxide are added to a mixed solution and continuously magnetically stirred to form a solution A;

[0011] (1.2) adding any two transition metal salt materials into a mixed solvent to obtain solution B and solution C;

[0012] (1.3) Mix solutions B and C to form solution D, then slowly add solution D dropwise into solution A and stir magnetically to form solution E;

[0013] (1.4) Add ascorbic acid dropwise to the E solution, stir magnetically and let stand until precipitation is complete, collect the product TM-MNPs, wash with acetic acid, collect the sample by centrifugation, repeat 3-5 times, then wash with alcohol, collect the sample by centrifugation, repeat 3-5 times, then wash with water, collect the sample by centrifugation, repeat 3-5 times, and then vacuum dry for use;

[0014] (2) Preparation of binary and multi-component TM-MNPs@MgH2 composite hydrogen storage materials

[0015] The TM-MNPs material is pre-ball-milled, and then the TM-MNPs are mixed with MgH2 and ball-milled again. The mixture powder is kept at 150°C under vacuum for 3-6 hours, and then heated to 400-550°C under vacuum and kept for 1-3 hours until complete dehydrogenation is formed to form a binary FeCo-MNPs@MgH2 composite hydrogen storage material.

[0016] Furthermore, the transition metal described in the present invention is selected from salts corresponding to any two or more of the following metals: Ni, Fe, Co, Cu, Zn, Ag, La, Mn, Cr, Ti, Pt, Cd, Pd, Mo, Ru, Nb, Zr, Y, Sc, and V.

[0017] Furthermore, the salt includes nitrate, sulfate, chloride, acetate and hydrates thereof.

[0018] Further, the volume ratio of dioctyldimethylammonium chloride to sodium hydroxide in step (1.1) is 10-100 μL:5-50;

[0019] The concentration of the sodium hydroxide is 10M;

[0020] The mixed solution is obtained by mixing water and ethanol in a volume ratio of 7:3;

[0021] The magnetic stirring rate is 400-1000 rpm, and the magnetic stirring time is 1-4 h.

[0022] Furthermore, the molar mass ratio of any two metal salt materials in step (1.2) is 1:1, and the volume ratio of the molar mass of any one metal salt material to dioctyldimethylammonium chloride is 3mmol:10-100μL;

[0023] The mixed solvent is a mixed solvent of ethanol and water, and the mass proportion of ethanol in the mixed solvent is 0-100%;

[0024] Furthermore, in step (1.3), the magnetic stirring rate is 300-1000 rpm, and the magnetic stirring time is 3 h.

[0025] Furthermore, in step (1.4), the volume ratio of ascorbic acid to dioctyldimethylammonium chloride is 1-10.0 mL: 10-100 μL, and the concentration of ascorbic acid is 0.1 M;

[0026] The magnetic stirring rate is 500-1000 rpm, and the magnetic stirring time is 1-6 h

[0027] The standing temperature is 25°C and the standing time is 1-6 hours

[0028] The vacuum drying temperature is 80-100° C., and the vacuum drying time is 24-72 hours.

[0029] Furthermore, the pre-milling rate in step (2) is 100-200 rpm, and the pre-milling time is 1-4 h;

[0030] The mass ratio of FeCo-MNPs to MgH2 is 1:9;

[0031] The ball milling rate is 150-300 rpm, and the ball milling time is 4-8 h.

[0032] The beneficial effects of the present invention are as follows: compared with pure MgH2 hydrogen storage materials, the binary and multi-component TM-MNPs@MgH2 magnesium-based composite hydrogen storage materials prepared by the present invention have a smaller reduction in hydrogen storage capacity, a significantly reduced hydrogen absorption and desorption reaction temperature, and greatly improved kinetics; compared with the traditional MgH2 multi-component catalytic hydrogen storage material preparation process, the preparation process of the present invention is simple, the material synergistic catalytic efficiency is good, the operability is strong, the preparation cycle is short, and the output rate is high; the required raw materials are cheap and easy to obtain, the preparation process cost is low and the safety is high, and it is suitable for industrial mass production.

[0033] In summary, the binary and multi-component mesoporous nano-microsphere catalyst systems prepared by this method are ultimately uniformly distributed in nanometer size, which greatly improves the catalytic efficiency, effectively reduces the amount of catalyst added, saves costs, and greatly increases the hydrogen storage capacity of the material under working conditions.

[0034] The mesoporous nano-microspheres loaded with binary and multi-catalytic elements and the subsequent composite hydrogen storage materials in the present invention are prepared at room temperature and pressure under mild conditions, with simple operation, safe and controllable, no high energy consumption, and stable material properties and easy processing.

[0035] The present invention does not require strict isolation of water and oxygen for preparing high-performance hydrogen storage materials, has no other by-products, has strong operational safety, and is low-cost and high-yield, and is very suitable for industrial promotion and industrial preparation and application of 100-kilogram-level high-efficiency solid-state hydrogen storage powder systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is a TEM image of the FeCo-MNPs catalyst synthesized by the present invention;

[0037] Figure 2 It is the XRD spectrum of the FeCo-MNPs@MgH2 composite hydrogen storage material synthesized in the present invention in the hydrogen absorption state.

[0038] Figure 3 Bright field image (a), HAADF dark field image (b), high-resolution image (c, d), and EDS energy spectrum of Mg, Fe, Co, and O elements (ei) of FeCo-MNPs@MgH2 composite hydrogen storage particles.

[0039] Figure 4 It is the isothermal hydrogen absorption curve of FeCo-MNPs@MgH2 high performance hydrogen storage material at a series of temperatures;

[0040] Figure 5 It is the fitting value of hydrogen absorption activation energy of FeCo-MNPs@MgH2 high performance hydrogen storage material under JMAK model. Figure 6 This is the DSC curve of FeCo-MNPs@MgH2 high performance hydrogen storage material at different heating rates Figure 7 It is the ln(β / T of FeCo-MNPs@MgH2 high performance hydrogen storage material. p 2 )vs.1000 / T p Fitting plot. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1 A magnesium-based composite hydrogen storage material based on multi-catalyst nanoclusters

[0043] (1) Preparation of binary transition metals (TM) FeCo-MNPs

[0044] First, 20 μL of dioctyldimethylammonium chloride (BDAC) and 50 μL of sodium hydroxide (NaOH) (10 M) were added to 50 mL of a mixed solution (water / ethanol volume ratio of 7:3), and magnetic stirring was continued at 600 rpm for 2 h to form solution A.

[0045] 3mmol Fe(NO3)3·9H2O (1.212g) and 3mmol Co(NO3)2·6H2O (0.875g) were dissolved in 50ml of a mixed solvent consisting of deionized water and anhydrous ethanol to obtain solutions B and C, respectively. Here, the mass proportion of ethanol in the mixed solvent is 70%.

[0046] The B and C solutions were mixed evenly to form a solution D, and then the D solution was slowly added dropwise to the A solution, and magnetic stirring was performed at 500 rpm for 3 h to form a solution E;

[0047] 5.0 mL of ascorbic acid (AA 0.1 M) was added dropwise to the E solution, and the solution was stirred magnetically at 700 rpm for 2 h and allowed to stand at 25 °C for 6 h. Finally, after the precipitation was completed, the product FeCo-MNPs was collected, washed with acetic acid, and the sample was collected by centrifugation, which was repeated 3-5 times. Then, the sample was washed with alcohol, and the sample was collected by centrifugation, which was repeated 3-5 times. Then, the sample was washed with water, and the sample was collected by centrifugation, which was repeated 3-5 times. The sample was dried under vacuum at 90 °C for 48 h and then used.

[0048] (1.4) Add ascorbic acid dropwise to the E solution, stir magnetically and let stand until precipitation is complete, collect the product TM-MNPs, wash with acetic acid, collect the sample by centrifugation, repeat 3-5 times, then wash with alcohol, collect the sample by centrifugation, repeat 3-5 times, then wash with water, collect the sample by centrifugation, repeat 3-5 times, and then vacuum dry for use;

[0049] (2) Preparation of binary FeCo-MNPs@MgH2 composite hydrogen storage materials

[0050] The binary FeCo-MNPs material was pre-ball-milled at 150 rpm for 2 h, and MgH2 powder material (purity ≥ 98%) was added at a mass ratio of FeCo-MNPs:MgH2 = 1:9, and ball-milled at 2300 rpm for 6 h. The mixed powder was then kept at 150°C for 4 h under vacuum, and then heated to 450°C under vacuum and kept for 2 h until complete dehydrogenation was formed to form a binary FeCo-MNPs@MgH2 composite hydrogen storage material.

[0051] As shown in the accompanying drawings of the present invention, the morphology of the synthesized FeCo-MNPs is as follows: Figure 1 As shown by Figure 1It can be seen that bis(octyldimethylammonium chloride) (BDAC) with two hydrophobic tails and one hydrophilic head is used as a template for the mesoporous structure. Two different metal precursors, Fe and Co, are fixed and guided to be adsorbed on the template in a water / ethanol mixed solvent, and grow in situ along the mesoporous columnar direction to form monodisperse bimetallic mesoporous nanospheres, which exhibit a regular spherical structure with a diameter of about 50 nanometers.

[0052] Figure 2 This is the XRD spectrum of the FeCo-MNPs@MgH2 composite in the hydrogen absorption state. It can be seen that the FeCo-MNPs@MgH2 composite synthesized by the present invention has good crystallinity. In addition to the diffraction peak of the parent phase MgH2 / Mg for hydrogen absorption and desorption, the presence of the CoFe intermetallic compound catalyst is also detected in the composite, which proves that in the high-temperature hydrogen absorption and desorption reaction, the Fe and Co elements are combined to form the intermetallic compound CoFe as a catalyst, which greatly improves the kinetic properties of the composite.

[0053] Figure 3 These are the bright field image (a), HAADF dark field image (b), high-resolution image (c, d), and EDS energy spectrum of Mg, Fe, Co, and O elements of FeCo-MNPs@MgH2 high-performance hydrogen storage particles. The existence of CoFe intermetallic compound phase can be determined through the high-resolution image CoFe (110) crystal plane spacing information.

[0054] Figure 4 , Figure 5 The isothermal hydrogen absorption curves of FeCo-MNPs@MgH2 high performance hydrogen storage materials at different temperatures and the hydrogen absorption activation energy fitting curve under the JMAK model. Figure 4 It can be seen that as the temperature decreases, the amount and rate of hydrogen absorption do not decrease significantly. This is mainly due to its fine particles and good catalytic efficiency, which improves the dissociation of reaction hydrogen molecules, the diffusion rate of hydrogen atoms in the bulk phase and the character of the new phase, thereby obtaining excellent hydrogen absorption kinetics. Figure 5 The fitting results show that the hydrogen absorption activation energy Ea of the complex is 53.3±3.2 kJ / mol H2, which is significantly lower than that of pure magnesium (100.7±5.2 kJ / mol H2).

[0055] Figure 6 , Figure 7 They are the DSC curves of FeCo-MNPs@MgH2 high performance hydrogen storage materials at different heating rates and the corresponding ln(β / T p 2 )vs.1000 / Tp fitting curve, by Figure 6It can be seen that the peak temperatures of the composite at the heating rates of 10K / min, 5K / min and 3K / min were measured to be 564.1, 551.8 and 538.4K respectively, and its dehydrogenation temperature was significantly lower than that of pure magnesium hydride. Figure 7 The Kissinger equation for ln(β / T p 2 )-1000 / T p The curve was fitted to obtain the activation energy E of the hydrogen release reaction of FeCo-MNPs@MgH2 d The activation energy of hydrogen desorption is 108.1±11.6 kJ / mol H2, which is significantly lower than the activation energy of hydrogen desorption reaction of pure MgH2 (181.4±9.2 kJ / mol H2). From the DSC hydrogen desorption peak data and the hydrogen desorption activation energy data obtained by fitting, it can be seen that the hydrogen desorption kinetic rate of FeCo-MNPs@MgH2 composite is significantly improved due to the introduction of FeCo-MNPs catalytic system.

[0056] Example 2 A magnesium-based composite hydrogen storage material based on multi-catalyst nanoclusters

[0057] (1) Preparation of binary transition metals (TM) NiCo-MNPs

[0058] First, 20 μL of dioctyldimethylammonium chloride (BDAC) and 50 μL of sodium hydroxide (NaOH) (10 M) were added to 50 mL of a mixed solution (water / ethanol volume ratio of 7:3), and magnetic stirring was continued at 1000 rpm for 1-4 h to form solution A.

[0059] 3mmol Ni(NO3)2·6H2O and 3mmol Co(NO3)2·6H2O were dissolved in 50ml of a mixed solvent consisting of deionized water and anhydrous ethanol to obtain solutions B and C, respectively. Here, the mass proportion of ethanol in the mixed solvent is 70%.

[0060] The B and C solutions were mixed evenly to form a solution D, and then the D solution was slowly added dropwise to the A solution, and magnetic stirring was performed at 300 rpm for 3 h to form a solution E;

[0061] Then, 50 mL of ascorbic acid (AA 0.1 M) was added dropwise to the E solution, magnetically stirred at 500 rpm for 6 h, and allowed to stand at 25 ° C for 2 h. Finally, after the precipitation was completed, the product NiCo-MNPs was collected, washed with acetic acid, and centrifuged to collect the sample, repeated 3-5 times, then washed with alcohol, centrifuged to collect the sample, repeated 3-5 times, then washed with water, centrifuged to collect the sample, repeated 3-5 times, and then vacuum dried at 100 ° C for 24 h for use.

[0062] (2) Preparation of binary NiCo-MNPs@MgH2 composite hydrogen storage materials

[0063] The binary NiCo-MNPs material was pre-ball-milled at 200 rpm for 1 h, and MgH2 powder material (purity ≥ 98%) was added at a mass ratio of NiCo-MNPs:MgH2=1:9, and ball-milled at 300 rpm for 8 h. The mixture powder was kept at 150°C under vacuum for 3 h, then heated to 550°C under vacuum and kept for 1 h until complete dehydrogenation was formed to form a binary NiCo-MNPs@MgH2 composite hydrogen storage material.

[0064] Test Example 1

[0065] The product prepared in Example 1 of the present invention was compared with the product of the prior art, and the results are as follows:

[0066] Prior art 1: RAVarin, S.Li, Ch.Chiu, L.Guo, O.Morozova, T.Khomenko, Z.Wronski, J.Alloys Compd.404-406(2005)494-498.

[0067] Prior art 2: C. Lu, JX Zou, XQ Zeng, WJ Ding, Int. J. Hydrogen Energy 42 (2017) 15246-15255.

[0068] Prior art 3: ZW Ma, JX Zou*, D. Khan. Journal of Materials Science & Technology, 35 (2019) 2132-2143.

[0069] 1.1 Compared with the prior art 1, the dehydrogenation DSC test results of the FeCo-MNPs@MgH2 high-performance hydrogen storage material prepared by the present invention show that its peak dehydrogenation temperature at a heating rate of 3K / min is 538.4K, which is significantly lower than the Mg-Fe catalytic system in document 1 (584.8K). On the other hand, the comparison sample in the prior art 1 needs to be ball milled for a long time in a hydrogen atmosphere for 210 hours, and the preparation time and preparation operation are significantly higher than the preparation time of the composite of the present invention (4-8h). This shows that the nanocatalytic system of the present invention not only has a simpler preparation process and low energy consumption, but also can significantly improve the catalytic performance of the catalytic element through the construction of the nanocatalytic system.

[0070] 1.2 Prior art 2 prepares a Mg-Co hydrogen storage system by plasma arc. Compared with its isothermal hydrogen absorption curve, the hydrogen absorption rate of the composite sample prepared by the present invention at various temperatures is higher than that of the Mg-Co system in prior art 2. The activation energy of hydrogen absorption of the FeCo-MNPs@MgH2 high-performance hydrogen storage material is Ea, which is 53.3 kJ / mol H2, significantly lower than the Ea of 73.2 kJ / mol H2 of the Mg-Co material in prior art 2. The peak dehydrogenation temperature of the Mg-Co system is 633K, while the peak dehydrogenation temperature of the FeCo-MNPs@MgH2 high-performance hydrogen storage material of the present invention is 538.4K, which is much lower than that of the sample. This shows that the dual-element catalytic system prepared by the present invention can more efficiently improve the hydrogen absorption and desorption kinetics of the matrix.

[0071] 1.3 Prior Art 3 introduces Fe-Co based catalytic system through MOFs material to form MgH2-Co MOF and MgH2-FeMOF composites. The hydrogen absorption activation energies of the two samples are 73.9±2.0 and 66.8±3.3 kJ / mol H2, while the hydrogen absorption activation energy Ea of the FeCo-MNPs@MgH2 high performance hydrogen storage material of the present invention is significantly reduced to 53.3 kJ / mol H2. The peak dehydrogenation temperatures of the two composites in Prior Art 3 at a heating rate of 3K / min are 635.7 and 614.6K, and correspondingly, the dehydrogenation activation energies of the two samples of MgH2-Co MOF and MgH2-Fe MOF are 142.3±6.5 kJ / mol H2 and 151.3±9.4 kJ / mol H2. The peak temperature of the FeCo-MNPs@MgH2 in the present invention at the same heating rate is 538.4K, which is significantly lower than that of the MgH2-Co MOF and MgH2-Fe MOF samples in Reference 3, and the activation energy E of the hydrogen desorption reaction of FeCo-MNPs@MgH2 is d It is 108.1±11.6 kJ / mol H2, which is significantly lower than the activation energy of the hydrogen desorption reaction of pure MgH2 (181.4±9.2 kJ / mol H2) and the dehydrogenation activation energy of the two samples in the prior art 3, indicating that the high-efficiency binary catalyst obtained by the preparation method of the present invention can more efficiently improve the comprehensive hydrogen absorption and desorption kinetics of magnesium-based hydrogen storage materials.

[0072] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a magnesium-based composite hydrogen storage material based on multi-catalyst nanoclusters, characterized in that: The following steps are involved: (1) Preparation of binary and multi-element transition metal TM-MNPs (1.1) First, dioctyldimethylammonium chloride and sodium hydroxide are added to a mixed solution and continuously magnetically stirred to form a solution A; (1.2) adding any two transition metal salt materials into a mixed solvent to obtain solution B and solution C; (1.3) Mix solutions B and C to form solution D, then slowly add solution D dropwise into solution A and stir magnetically to form solution E; (1.4) Add ascorbic acid dropwise to the E solution, stir magnetically and let stand until precipitation is complete, collect the product TM-MNPs, wash with acetic acid, collect the sample by centrifugation, repeat 3-5 times, then wash with alcohol, collect the sample by centrifugation, repeat 3-5 times, then wash with water, collect the sample by centrifugation, repeat 3-5 times, and then vacuum dry for use; (2) Preparation of binary and multi-component TM-MNPs@MgH2 composite hydrogen storage materials The TM-MNPs material is pre-ball-milled, and then the TM-MNPs are mixed with MgH2 and ball-milled again. The mixture powder is kept at 150°C under vacuum for 3-6 hours, and then heated to 400-550°C under vacuum and kept for 1-3 hours until complete dehydrogenation is formed to form a binary FeCo-MNPs@MgH2 composite hydrogen storage material.

2. The method for preparing a magnesium-based composite hydrogen storage material based on multi-catalyst nanoclusters according to claim 1, characterized in that: The transition metal is selected from salts corresponding to any two or more of the following metals: Ni, Fe, Co, Cu, Zn, Ag, La, Mn, Cr, Ti, Pt, Cd, Pd, Mo, Ru, Nb, Zr, Y, Sc, and V.

3. The method for preparing a magnesium-based composite hydrogen storage material based on multi-catalyst nanoclusters according to claim 1, characterized in that: The volume ratio of dioctyldimethylammonium chloride to sodium hydroxide in step (1.1) is 10-100 μL:5-50; The concentration of the sodium hydroxide is 10M; The mixed solution is obtained by mixing water and ethanol in a volume ratio of 7:3; The magnetic stirring rate is 400-1000 rpm, and the magnetic stirring time is 1-4 h.

4. The method for preparing a magnesium-based composite hydrogen storage material based on multi-catalyst nanoclusters according to claim 1, characterized in that: The molar mass ratio of any two metal salt materials in step (1.2) is 1:1, and the volume ratio of the molar mass of any one metal salt material to dioctyldimethylammonium chloride is 3mmol:10-100μL; The mixed solvent is a mixed solvent of ethanol and water, and the mass proportion of ethanol in the mixed solvent is 0-100%.

5. The method for preparing a magnesium-based composite hydrogen storage material based on multi-catalyst nanoclusters according to claim 1, characterized in that: The magnetic stirring rate in step (1.3) is 300-1000 rpm, and the magnetic stirring time is 3 h.

6. The method for preparing a magnesium-based composite hydrogen storage material based on multi-catalyst nanoclusters according to claim 1, characterized in that: The volume ratio of ascorbic acid to dioctyldimethylammonium chloride in step (1.4) is 1-10.0 mL: 10-100 μL, and the concentration of ascorbic acid is 0.1 M; The magnetic stirring rate is 500-1000 rpm, and the magnetic stirring time is 1-6 h The standing temperature is 25°C and the standing time is 1-6 hours The vacuum drying temperature is 80-100° C., and the vacuum drying time is 24-72 hours.

7. The method for preparing a magnesium-based composite hydrogen storage material based on multi-catalyst nanoclusters according to claim 1, characterized in that: The pre-milling rate in step (2) is 100-200 rpm, and the pre-milling time is 1-4 h; The mass ratio of FeCo-MNPs to MgH2 is 1:9; The ball milling rate is 150-300 rpm, and the ball milling time is 4-8 h.

8. A magnesium-based composite hydrogen storage material based on multi-catalyst nanoclusters, characterized in that: Prepared by the method according to any one of claims 1 to 7.

Citation Information

Cited By

  • Modified magnesium hydride composite hydrogen storage material and preparation method thereof

    CN120757069A